Method for recovering target metal in positive electrode material of lithium battery

By using a composite solvent system of citric acid and bisazole ligand and a surface-modified magnetic adsorbent, the problems of low leaching efficiency and poor selectivity in the recycling of the positive electrode material of lithium batteries are solved, and the target metal recovery is achieved with an efficient, economical and environmentally friendly target metal recovery.

CN119144838BActive Publication Date: 2025-03-07GANZHOU JIRUI NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411671152.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

In the existing lithium battery positive electrode material recycling technology, the leaching efficiency is low, the selectivity is poor, and the use of strong acids has high requirements for equipment and environment, which increases operating costs and environmental pressure.

Method used

A composite solvent system consisting of citric acid and an organic ligand containing two alumina heterocycles is used to achieve efficient leaching of the target metal ions under appropriate acid conditions, and efficient enrichment and rapid separation of the target metal ions are carried out by magnetic adsorbents with phosphate and/or sulfonic acid groups on the surface.

Benefits of technology

The leaching efficiency and selectivity of the target metal are improved, the operating cost and environmental pressure are reduced, and the recovery rate and recycling purity are high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144838B_ABST
    Figure CN119144838B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for recovering target metals in positive electrode materials of lithium batteries, the method comprising: obtaining positive electrode material particles after pre-treating lithium batteries; adding the particles to a composite solvent composed of citric acid and dinitrogen heterocyclic ligands, leaching target metal ions, and obtaining a leachate; adding a magnetic adsorbent whose surface is modified with phosphate groups and / or sulfonic acid groups, so that the target metal ions are enriched on the adsorbent; applying a magnetic field to separate the magnetic adsorbent enriched with target metal ions. The method for recovering target metals in positive electrode materials of lithium batteries provided by the present invention can achieve efficient leaching of target metal ions by using a composite solvent system composed of citric acid and an organic ligand containing two nitrogen heterocyclic rings; at the same time, a magnetic adsorbent whose surface is modified with phosphate groups or sulfonic acid groups is used to achieve efficient enrichment of target metal ions, and can achieve rapid separation under an external magnetic field; and the recovery rate and recovery purity of the method are both high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of waste battery recycling and treatment, and in particular relates to a method for recycling target metals in lithium battery positive electrode materials. Background Art

[0002] In the current recycling process of lithium-ion batteries, the recovery of valuable metals (such as cobalt, nickel and manganese) in retired lithium battery cathode materials has important economic value and environmental significance. However, the existing cathode material recycling technology has many problems, making the efficient recycling process face great challenges.

[0003] The leaching efficiency of existing technologies is generally low during the leaching process, especially when recovering transition metals such as cobalt and nickel. Traditional methods usually use inorganic acids (such as sulfuric acid, nitric acid, etc.) for metal leaching. Although these methods have certain dissolving capabilities, they often require high acidic conditions, resulting in a slow leaching process of the material and unsatisfactory efficiency. At the same time, the use of strong acids has high requirements for equipment and the environment, increasing operating costs. Many studies have shown that although strong acids are effective in leaching lithium battery positive electrode materials, their corrosiveness to the environment and complexity of handling limit the possibility of their large-scale application.

[0004] In addition, the problem of poor selectivity in the leaching process is also very prominent. In addition to target metals such as cobalt and nickel, lithium battery positive electrode materials also contain impurity metals such as aluminum and iron. Relying solely on strong acid or a single organic acid for leaching often leads to the dissolution of multiple metals at the same time, lacking selectivity for the target metal. This situation not only increases the difficulty of subsequent separation of the leachate, but also reduces the purity of the target metal, resulting in a further decrease in recovery efficiency. Especially under high-concentration acidic conditions, the amount of impurity metal dissolved is high, which significantly increases the demand for separation and purification processes in the subsequent purification process.

[0005] Therefore, it is necessary to provide a new solution to the above technical problems. Summary of the invention

[0006] The object of the present invention is to provide a method for recovering target metals in lithium battery positive electrode materials, which can solve the problems of low leaching efficiency and poor selectivity in recovering valuable metals in lithium battery positive electrode materials.

[0007] To achieve the above purpose, the technical solution provided by the present invention is as follows:

[0008] The invention provides a method for recovering target metals in positive electrode materials of lithium batteries, wherein the target metals include cobalt, nickel and manganese, and the method includes: pre-treating a lithium battery to obtain positive electrode material particles; adding the positive electrode material particles into a composite solvent, adjusting the pH to 3.3-5, leaching target metal ions and obtaining a leachate; the composite solvent includes citric acid and an organic ligand containing two nitrogen heterocycles; adding a magnetic adsorbent into the leachate, adjusting the pH to 1-2.7, enriching the target metal ions on the magnetic adsorbent, and forming a mixed solution; the surface of the magnetic adsorbent is modified with a phosphate group and / or a sulfonic acid group; applying a magnetic field to the mixed solution to separate the magnetic adsorbent enriched with the target metal ions from the mixed solution.

[0009] In one or more embodiments, the method of pre-treating the lithium battery includes: after the lithium battery is fully discharged, disassembling and separating the positive electrode material; crushing and screening the positive electrode material to obtain positive electrode material particles with a particle size of less than 100 μm.

[0010] In one or more embodiments, the mass ratio of the positive electrode material particles to the composite solvent is 1: (10~20); and / or the concentration of citric acid in the composite solvent is 0.5~1.5 mol / L; and / or the molar ratio of the organic ligand to the target metal ion in the composite solvent is (1~2): 1.

[0011] In one or more embodiments, the organic ligand includes at least one of 2,2'-bipyridine and 1,10-phenanthroline.

[0012] In one or more embodiments, the composite solvent is prepared by: dissolving citric acid in deionized water to obtain a citric acid solution; dissolving an organic ligand in ethanol to obtain an organic ligand solution; and mixing the citric acid solution and the organic ligand solution to obtain a composite solvent.

[0013] In one or more embodiments, the magnetic adsorbent includes magnetic carbon nanotubes attached with cobalt and / or nickel nanoparticles.

[0014] In one or more embodiments, the preparation method of the magnetic carbon nanotubes includes: refluxing the carbon nanotubes in a mixed acid composed of sulfuric acid and nitric acid for 2 to 6 hours for acidification; dispersing the acidified carbon nanotubes in a cobalt and / or nickel metal salt solution, ultrasonically treating for 3 to 8 hours to obtain a carbon nanotube suspension; adding sodium hydride to the carbon nanotube suspension under ice bath conditions, stirring the reaction, so that the cobalt and / or nickel metal ions are reduced to metal nanoparticles, which are attached to the surface of the carbon nanotubes; centrifuging and collecting the product, washing and drying, to obtain magnetic carbon nanotubes.

[0015] In one or more embodiments, the magnetic adsorbent includes magnetic polymer microspheres having magnetic nanoparticles embedded therein.

[0016] In one or more embodiments, the preparation method of the magnetic polymer microspheres includes: dispersing magnetic nanoparticles in an ethanol solution, adding polyvinyl alcohol, and ultrasonically dispersing for 30 minutes to obtain a magnetic nanoparticle suspension; mixing styrene, methacrylic acid and divinylbenzene monomers in proportion to obtain a monomer mixture; adding the monomer mixture to the magnetic nanoparticle suspension, stirring evenly, and then adding an initiator; stirring the reaction at 65~75°C and an inert protective atmosphere for 6~8 hours to polymerize styrene, methacrylic acid and divinylbenzene monomers on the surface of the magnetic nanoparticles; centrifuging and collecting the product, washing and drying, to obtain magnetic polymer microspheres.

[0017] In one or more embodiments, the method further includes: washing the separated magnetic adsorbent enriched with target metal ions; adding the washed magnetic adsorbent to an ethylenediaminetetraacetic acid solution to dissociate the target metal ions enriched on the magnetic adsorbent to obtain a dissociation solution; applying a magnetic field to the dissociation solution to separate the magnetic adsorbent from the dissociation solution.

[0018] Compared with the prior art, the method for recovering target metals in lithium battery positive electrode materials provided by the present invention uses a composite solvent system composed of citric acid and an organic ligand containing two nitrogen heterocycles to achieve efficient leaching of target metal ions under appropriate acidic conditions, wherein citric acid provides a stable acidic environment and the dinitrogen heterocycle ligand enhances the selective complexation of cobalt, nickel and manganese; at the same time, a magnetic adsorbent with a surface modified with phosphate and / or sulfonic acid groups is used to achieve efficient enrichment of target metal ions through pH adjustment, and rapid separation is achieved under an external magnetic field; and the recovery rate and recovery purity of this method are both high. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some implementation methods recorded in the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 The present invention is a flowchart of a method for recovering target metals from positive electrode materials of lithium batteries according to an embodiment of the present invention. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0022] It should be noted that, unless otherwise indicated, all numbers used in the specification and claims to represent feature sizes, quantities and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.2, 1.4, 1.55, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0023] The recycling method of the present invention is proposed based on an in-depth analysis of existing lithium battery positive electrode material recycling technologies. Current technologies face several main problems when processing retired lithium-ion battery positive electrode materials: first, the efficiency during the leaching process is low, and existing methods mostly rely on strong acid solvents, which often require harsh reaction conditions and high energy consumption and equipment requirements; second, the selectivity is insufficient, and most solvents cannot effectively distinguish between target metals and impurity metals during the leaching process, resulting in cumbersome subsequent purification steps; in addition, the process flow is relatively complex, especially in multi-step extraction and waste liquid treatment, which not only has many operating steps, but also has great environmental pressure. Therefore, in response to these problems, the present invention proposes a recycling method that combines high efficiency, selectivity and simplicity.

[0024] The technical implementation idea of ​​the present invention is mainly to achieve efficient and selective leaching effects through a composite solvent system, and to complete the separation and enrichment of metal ions with the assistance of magnetic adsorbents and external magnetic fields. In the leaching stage, a specific composite solvent system is used to improve the dissolution and complexing efficiency of the target metal ions by combining appropriate acidity and organic ligands to form a relatively stable complex, ensuring that the metal can be effectively leached under mild conditions. At the same time, through selective complexation, the dissolution of impurity metals is reduced, thereby achieving selective leaching. In the metal enrichment stage, by adjusting the solution conditions, the complex is dissociated into target metal ions, and these ions are then selectively adsorbed on the magnetic adsorbent. The external magnetic field can further assist in the rapid separation of the adsorbent and simplify the process flow.

[0025] The implementation idea improves the leaching efficiency through the design of composite solvents, achieves high-purity recovery through selective complexation and magnetic separation, and improves the operational simplicity and environmental friendliness of the entire process by simplifying the separation steps. The recycling scheme of the present invention has significant advantages in terms of economy and environmental friendliness, and provides an improved path for the efficient recovery of retired lithium battery positive electrode materials.

[0026] Please refer to Figure 1 FIG. 1 is a flow chart of a method for recovering target metals in positive electrode materials of lithium batteries in one embodiment of the present invention. The method for recovering target metals in positive electrode materials of lithium batteries includes recoverable target metals such as cobalt, nickel, and manganese. The method specifically includes the following steps:

[0027] S101: pre-treating the lithium battery to obtain positive electrode material particles.

[0028] The implementation of step S101 specifically includes discharging, disassembling, separating, crushing and screening the positive electrode materials of the lithium battery. Its main goal is to ensure the safe and efficient recovery of the positive electrode materials and increase their specific surface area, thereby providing a good physical basis for the subsequent leaching process of metal ions.

[0029] In an exemplary embodiment, the method of pre-treating the lithium battery specifically includes: after the lithium battery is fully discharged, disassembling and separating the positive electrode material; crushing and screening the positive electrode material to obtain positive electrode material particles with a particle size of less than 100 μm.

[0030] The pretreatment process mainly includes two core steps: disassembling and separating the positive electrode material after the lithium battery is fully discharged, and crushing and screening the positive electrode material to obtain positive electrode material particles with a particle size of less than 100μm.

[0031] Lithium batteries usually retain some power when they are retired, and direct disassembly may cause dangers such as short circuits, sparks, and even combustion. Therefore, releasing the residual power in the battery through discharge processing can significantly reduce these safety risks.

[0032] Discharge methods generally include solution discharge and load resistance discharge. In solution discharge, the lithium battery can be placed in an electrolyte solution, and the charge in the battery is released by ion conduction, so that it gradually reaches a state of zero voltage. Another method is to connect the battery to a resistance load by connecting a suitable resistance load, and use a voltage monitoring device to monitor the battery voltage. When the voltage drops to 0V, the discharge process is completed.

[0033] After the discharge is completed, the battery can be disassembled and separated. This process includes the disassembly of the battery shell and the extraction of the electrode material. During the disassembly process, the battery shell, diaphragm, electrolyte, and positive and negative electrode materials need to be separated to obtain the positive electrode material rich in valuable metals. Disassembly usually includes steps such as mechanical crushing, shelling and separation. For example, the battery can be cut open by a mechanical cutting machine, and after removing the shell, the positive electrode material can be separated from other components by centrifugal separation or screening technology.

[0034] After disassembling, the battery will release materials with different components including positive electrode, negative electrode, separator and electrolyte. Among them, the positive electrode material is the focus of recycling. These positive electrode materials are rich in valuable metals such as cobalt, nickel and manganese.

[0035] After the positive electrode material is separated, it needs to be crushed and screened. The main purpose of crushing is to break the positive electrode material into a suitable particle size to increase its specific surface area, thereby improving the chemical reaction efficiency in the subsequent leaching process.

[0036] During the pulverization process, equipment such as ball mills or high-pressure crushers can be used, which can control the particle size of the positive electrode material to below 100μm. Smaller particles have a larger specific surface area, which can ensure full contact between the leaching agent and the material, allowing the leaching agent to enter the particles faster and contact the metal ions, thereby improving the leaching speed and overall efficiency of the metal ions.

[0037] After crushing, the positive electrode material can be screened to ensure that the obtained positive electrode material particles have a uniform particle size distribution. By using a sieve with a certain aperture, screening out particles of appropriate size can effectively remove large particles and some impurities generated during the crushing process, thereby improving the uniformity and purity of the positive electrode material. The uniformity of screening helps the stability of the leaching process, because particles that are too large or too small will lead to uneven reactions, which in turn affects the leaching efficiency of metal ions.

[0038] S102: adding the positive electrode material particles into a composite solvent, adjusting the pH to 3.3-5, leaching the target metal ions, and obtaining a leachate; the composite solvent includes citric acid and an organic ligand containing two nitrogen heterocycles.

[0039] The core of step S102 is to use a specific composite solvent system to efficiently leach the target metal ions (such as cobalt, nickel, and manganese) in the pretreated positive electrode material particles, thereby obtaining a leachate rich in metal ions. The specific process of this step includes adding the positive electrode material particles to the composite solvent, adjusting the pH value of the solution to 3.3~5, and effectively promoting the dissolution and selective complexation of metal ions through the components in the composite solvent system (including citric acid and an organic ligand containing two nitrogen heterocycles). Through the precise ratio of the solvent system and the control of pH conditions, step S102 can achieve efficient dissolution and selective extraction of metal ions. The leachate can be obtained by separation methods such as filtration and centrifugation.

[0040] In a specific implementation method, the pretreated positive electrode material particles are first added to a pre-prepared composite solvent. The main components of the composite solvent include citric acid and an organic ligand having two nitrogen heterocyclic rings. Citric acid is an environmentally friendly and biodegradable organic acid that can provide H in the solution. + , and forms a preliminary complex with the metal ions through its carboxyl (-COOH) and hydroxyl (-OH). This complexation can increase the solubility of the target metal ions, thereby improving the leaching efficiency. At the same time, the acidity of citric acid helps the solution maintain a moderate pH range, providing a favorable environment for the dissolution of the target metal ions. In addition, choosing citric acid instead of strong acids (such as sulfuric acid, hydrochloric acid, nitric acid, etc.) can effectively reduce the corrosive effects on the equipment, reduce operational safety risks and processing costs.

[0041] Citric acid can provide sufficient H in the pH range of 3.3 to 5. + This can promote the dissolution of metal oxides and avoid excessive dissolution of non-target metals (such as iron and aluminum) caused by too low pH. Therefore, this acid adjustment helps to limit the dissolution of impurity metals and ensure the selective leaching of target metals.

[0042] Another key component of the composite solvent is an organic ligand containing two nitrogen heterocycles (such as 2,2'-bipyridine or 1,10-phenanthroline). The nitrogen atom in the molecular structure of this type of ligand has a lone pair of electrons and can form stable chelates with transition metal ions such as cobalt and nickel. Through selective complexation, this type of ligand has a higher affinity for the target metal ions, which helps to improve the selectivity of metal leaching.

[0043] Since the target metal ions (such as Co 2+ 、Ni 2+ ) have a higher affinity for complexation reaction with ligands, so they preferentially bind to ligands to form stable complexes. This selective complexation property reduces the dissolution of non-target metal ions, greatly improving the leaching rate of target metals such as cobalt, nickel, and manganese.

[0044] For example, the two nitrogen atoms of bipyridine molecules can bind to Co 2+ The metal ions such as cobalt and nickel form stable chelates, significantly reducing their free state concentration in the solution and enhancing the complex selectivity of the solution. This process not only improves the recovery purity of target metals such as cobalt and nickel, but also inhibits the dissolution of impurity metals (such as aluminum and iron), thereby simplifying the subsequent separation process and improving the quality of the leachate.

[0045] When the ligand forms a stable complex with the target metal ion, the free energy of the target metal ion is reduced and its solubility in the solution is increased. For non-target metals (such as aluminum, iron, etc.), the complex formed by the ligand and the target metal ion is less stable and more difficult to dissolve, thereby achieving selective dissolution of the target metal oxide / salt.

[0046] There is a synergistic effect between citric acid and the organic ligand. Citric acid forms a primary complex with the target metal ion to improve the solubility of the target metal ion; the organic ligand further forms a more stable complex with the target metal ion to enhance the leaching effect of the target metal ion in the solution.

[0047] The acidic environment of citric acid can accelerate the dissolution reaction of metal oxides and allow the target metal ions to enter the solution. At the same time, the carboxyl and hydroxyl groups of citric acid have a strong complexing effect on the target metal ions to form a preliminary complex. The addition of a bifunctional organic ligand containing two nitrogen heterocycles further allows the target metal ions to form a stable complex with the ligand, thereby maintaining a low free metal ion concentration in the solution. This dynamic equilibrium mechanism allows more target metal oxide oxides / salts to dissolve, increasing the overall leaching rate.

[0048] In the composite solvent system, the target metal ion quickly forms a complex with the ligand, thereby reducing the possibility of hydrolysis or precipitation. Once the target metal ion is complexed, it can remain in a stable state in the solution, avoiding the loss of the target metal due to hydrolysis. In addition, the stable complex reduces the probability of reverse precipitation, ensuring that the target metal ion can be efficiently and continuously dissolved from the positive electrode material.

[0049] The acidity adjustment in the composite solvent system and the selective complexation of the organic ligands keep the pH value in a range that is conducive to metal dissolution and complexation. The influence of extreme acidic or alkaline conditions on the equipment and reaction process is avoided, while the consumption of energy and cost is reduced, thereby achieving higher leaching efficiency under mild conditions.

[0050] If citric acid is lacking, the acidity in the solution is insufficient, and the dissolution rate of the target metal oxide / salt will be significantly reduced, resulting in a decrease in the efficiency of the target metal ions entering the solution. In addition, the initial complexation of citric acid with the target metal ions helps prevent the target metal ions from hydrolyzing and precipitating. Once citric acid is lacking, the stability of the target metal ions in the solution decreases, and it is easy to form insoluble precipitates under high pH conditions, further reducing the leaching efficiency.

[0051] The organic ligand contains two nitrogen heterocyclic rings. This structure can form highly stable chelates with target transition metal ions such as cobalt, nickel, and manganese, and thus has high complexation selectivity. The presence of organic ligands can reduce the activity of target metal ions, promote the dissolution of more target metal ions from the cathode material, and improve the leaching efficiency; at the same time, through selective complexation, organic ligands inhibit the dissolution of impurity metal ions, thereby improving the leaching efficiency of the target metal.

[0052] If there is a lack of organic ligands, the solution lacks a selectivity factor that can selectively complex target metals such as cobalt, nickel, and manganese, which will cause impurity metals (such as aluminum and iron) to enter the leachate, reducing the selectivity for the target metal. In addition, without the selective complexation of the target metal by the organic ligand, the target metal ions in the solution will reach saturation quickly, making it difficult to promote further metal dissolution, resulting in reduced leaching efficiency.

[0053] Citric acid and bifunctional organic ligands complement each other in the composite solvent system, respectively ensuring acidic conditions and selective complexation, ensuring that the target metal ions can be efficiently dissolved and maintained in solution under mild conditions. The acidity and preliminary complexation provided by citric acid reduce the difficulty of dissolving the target metal oxide / salt, while the selective complexation characteristics of the bifunctional ligand improve the selective dissolution of the target metal and prevent interference from impurities.

[0054] In the pH range of 3.3-5, the acidity of the solution is moderate, and citric acid can effectively release H + , promoting the dissolution of target metal oxides / salts (such as cobalt, nickel, and manganese oxides). The acidic environment can break the oxide crystal structure and allow the target metal ions to enter the solution, while avoiding the corrosive effects of strong acidity on the solution and the high amount of impurities dissolved. Within this pH range, the nitrogen atoms on the organic ligands are not completely protonated, retaining lone pairs of electrons, which can effectively form coordination bonds with transition metal ions and maintain complexing ability with the target metal. This combination promotes the dissolution of target metal oxides / salts and the selective release of target metal ions, ensuring a high leaching efficiency.

[0055] In an overly acidic environment with a pH value lower than 3.3, impurity metals such as aluminum and iron are easily dissolved into the solution, affecting the selective recovery of the target metal. The nitrogen heterocyclic sites of the organic ligands are easily protonated, reducing the complexing ability with the target metal. This will lead to a decrease in the stability of the target metal ions in the solution, making it difficult to form a stable complex, affecting the leaching selectivity and efficiency. When the pH value is higher than 5, the acidity is not enough to break the crystal structure of the metal oxide, resulting in limited release of the target metal ions and reduced leaching efficiency of the metal ions.

[0056] In an exemplary embodiment, the mass ratio of the positive electrode material particles to the composite solvent is 1: (10~20); and / or the concentration of citric acid in the composite solvent is 0.5~1.5 mol / L; and / or the molar ratio of the organic ligand to the target metal ion in the composite solvent is (1~2): 1.

[0057] The mass ratio of positive electrode material particles to composite solvent is 1:(10~20), that is, 10~20 units of composite solvent are required for every 1 unit mass of positive electrode material. This ratio ensures that the composite solvent can fully penetrate the surface of the positive electrode material particles, forming a sufficient reaction interface so that citric acid and organic ligands can effectively contact each particle. If the amount of solvent is too small and cannot completely cover the surface of the material particles, the reaction rate during the leaching process will decrease, the leaching will be incomplete, and the metal extraction efficiency will be reduced. On the other hand, excessive solvent not only wastes resources, but also increases the difficulty and cost of subsequent processing.

[0058] The concentration of citric acid is controlled at 0.5~1.5mol / L, which provides moderate acidity for the composite solvent to ensure effective dissolution of metal oxides during the leaching process. If the concentration of citric acid is lower than 0.5mol / L, the acidity is insufficient, the dissolution rate is reduced, and the leaching efficiency is reduced; while a concentration higher than 1.5mol / L may bring unnecessary excess acidity, increase the dissolution of impurity metals, and reduce the selectivity effect.

[0059] The molar ratio of the organic ligand to the target metal ion is set to (1~2):1, so that the organic ligand can effectively complex and stabilize the target metal ion in the solution. When the molar ratio of the organic ligand to the target metal ion is 1:1, single-molecule complexation can be achieved, and the target metal can be effectively complexed; while at 2:1, multi-molecule complexation helps to improve the stability of the complexation, and further enhances the dissolution and stability of the target metal in the acidic solution. If the molar ratio is lower than 1:1, it may lead to insufficient complexation, increased metal ion freeness, and reduced selectivity; if it is higher than 2:1, it will increase ligand consumption, increase costs, and the effect will not be significantly improved.

[0060] In an exemplary embodiment, the organic ligand includes at least one of 2,2'-bipyridine and 1,10-phenanthroline. 10 H8N2) and 1,10-phenanthroline (C 12 H8N2) molecules all contain two nitrogen heterocycles. The nitrogen atoms of these nitrogen heterocycles have lone pairs of electrons, which can bind to transition metal ions through coordination bonds to form stable complexes. Through this bidentate coordination, these ligands have extremely high selectivity, and the complexes formed with metal ions such as cobalt and nickel are more stable than impurity metals such as aluminum and iron. This selectivity reduces the solubility of impurity metal ions, allowing high-purity target metals to be obtained in the leachate, avoiding the complexity of subsequent separation and purification.

[0061] Under specific reaction conditions, the nitrogen atoms of 2,2'-bipyridine and 1,10-phenanthroline are not easily protonated, so they can still effectively complex with the target metal under weakly acidic conditions (pH 3.3~5), thereby achieving efficient leaching under mild conditions. Its high selectivity comes from the geometric structure and electronic distribution characteristics of the ligand, which can match the electronic structure and empty d orbital of transition metals such as cobalt and nickel, making its complexation strong and stable.

[0062] In an exemplary embodiment, the preparation method of the composite solvent includes: dissolving citric acid in deionized water to obtain a citric acid solution; dissolving an organic ligand in ethanol to obtain an organic ligand solution; and mixing the citric acid solution and the organic ligand solution to obtain a composite solvent.

[0063] S103: adding a magnetic adsorbent to the leachate, adjusting the pH to 1-2.7, so that the target metal ions are enriched on the magnetic adsorbent to form a mixed solution; the surface of the magnetic adsorbent is modified with phosphate groups and / or sulfonic acid groups.

[0064] It should be noted that under the condition of pH 1-2.7, organic ligands (such as 2,2'-bipyridine or 1,10-phenanthroline) are protonated and lose the ability to form stable complexes with target metal ions (such as cobalt, nickel, and manganese). This protonation destroys the coordination bond between the ligand and the metal ion, causing the metal ion to dissociate from the ligand and release into the solution. This process ensures that the target metal ions previously bound to the ligand can be free again and can bind to the phosphate and / or sulfonic acid groups on the surface of the adsorbent.

[0065] Phosphate (-PO4H2) and sulfonate (-SO3H) groups have high negative charge in low pH environments, which enables them to effectively adsorb positively charged metal ions. Phosphate and sulfonate groups have lone pairs of electrons and polarized oxygen atoms on their surfaces, which give them a strong affinity for transition metal ions such as cobalt, nickel, and manganese. Since these functional groups are stable in strongly acidic environments, they can efficiently enrich the target metal ions on the adsorbent surface and achieve selective adsorption.

[0066] In an exemplary embodiment, the magnetic adsorbent includes magnetic carbon nanotubes attached with cobalt and / or nickel nanoparticles. The preparation method of the magnetic carbon nanotubes includes: reflux the carbon nanotubes in a mixed acid composed of sulfuric acid and nitric acid for 2 to 6 hours for acidification; disperse the acidified carbon nanotubes in a cobalt and / or nickel metal salt solution, and ultrasonically treat for 3 to 8 hours to obtain a carbon nanotube suspension; add sodium hydride to the carbon nanotube suspension under ice bath conditions, stir the reaction, reduce the cobalt and / or nickel metal ions to metal nanoparticles, and attach them to the surface of the carbon nanotubes; collect the product by centrifugation, wash and dry, and obtain magnetic carbon nanotubes.

[0067] The first step in preparing magnetic carbon nanotubes is to reflux and acidify the carbon nanotubes in a mixture of sulfuric acid and nitric acid, usually for 2 to 6 hours. The purpose of the acidification process is to introduce oxygen-containing functional groups such as carboxyl (-COOH) and hydroxyl (-OH) on the surface of the carbon nanotubes, making their surface highly hydrophilic and active, thereby providing binding sites for the loading of metal nanoparticles. The combination of sulfuric acid and nitric acid can effectively remove impurities on the surface of carbon nanotubes and defects in the carbon atom chain, improve the purity and surface area of ​​carbon nanotubes, and create surface conditions for metal loading in subsequent steps.

[0068] The acidified carbon nanotubes are dispersed in a cobalt or nickel metal salt solution (such as cobalt nitrate or nickel nitrate) and treated under ultrasound for 3 to 8 hours to ensure that the metal ions can be evenly adsorbed on the surface of the carbon nanotubes. The core of this process is that the carbon nanotubes can fully contact the metal ions in the metal salt solution through the action of ultrasound. The action of ultrasound can fully disperse the carbon nanotubes in the solution to prevent them from agglomerating. At the same time, through mechanical oscillation, the metal ions form preliminary electrostatic adsorption on the surface of the carbon nanotubes, thereby achieving uniform distribution of the metal ions.

[0069] After the adsorption step is completed, the carbon nanotube suspension is placed in an ice bath (a low temperature environment close to 0°C), a reducing agent (such as sodium hydride NaH) is added and the reaction is stirred. The low temperature environment of the ice bath helps to control the rate of the reduction reaction and prevent the metal particles from agglomerating due to too fast a reaction. As a strong reducing agent, sodium hydride can effectively reduce the cobalt or nickel ions in the solution to a metallic state, so that they form nanoparticles on the surface of the carbon nanotubes and firmly adhere. After the reduction is completed, the residual reducing agent and other by-products are removed by centrifugation, and then washed with deionized water and ethanol multiple times to ensure the purity of the adsorbent, and finally dried in a vacuum drying oven to obtain the final magnetic carbon nanotubes.

[0070] The magnetic carbon nanotubes, as adsorbents, exhibit excellent magnetic properties due to the cobalt or nickel metal nanoparticles loaded on their surfaces. The magnetic properties enable the adsorbent to be quickly recovered through an external magnetic field after the adsorption process is completed, avoiding the complexity of traditional filtration and centrifugation operations.

[0071] In an exemplary embodiment, the magnetic adsorbent includes magnetic polymer microspheres, and the magnetic polymer microspheres are embedded with magnetic nanoparticles. The preparation method of the magnetic polymer microspheres includes: dispersing magnetic nanoparticles in an ethanol solution, adding polyvinyl alcohol, and ultrasonically dispersing for 30 minutes to obtain a magnetic nanoparticle suspension; mixing styrene, methacrylic acid and divinylbenzene monomers in proportion to obtain a monomer mixture; adding the monomer mixture to the magnetic nanoparticle suspension, stirring evenly, and adding an initiator; stirring the reaction at 65-75°C and an inert protective atmosphere for 6-8 hours to polymerize styrene, methacrylic acid and divinylbenzene monomers on the surface of the magnetic nanoparticles; centrifuging and collecting the product, washing and drying, and obtaining magnetic polymer microspheres.

[0072] The first step in the preparation method of magnetic polymer microspheres is to disperse magnetic nanoparticles (such as Fe3O4 particles) in an ethanol solution, add polyvinyl alcohol (PVA), and disperse them by ultrasonic for 30 minutes to obtain a uniform magnetic nanoparticle suspension. The purpose of this step is to ensure the uniform dispersion of nanoparticles, because nanoparticles have extremely high surface area and surface energy and are prone to agglomeration. Ethanol, as a solvent, can effectively reduce the mutual attraction between particles, and polyvinyl alcohol, as a stabilizer, forms a protective layer on the surface of nanoparticles to prevent particles from agglomerating in the solution.

[0073] Styrene, methacrylic acid and divinylbenzene monomers are mixed in proportion to obtain a monomer mixture. Styrene can form a strong polymer skeleton after polymerization, providing mechanical strength and stability of the microspheres; the introduction of methacrylic acid increases the hydrophilicity and active sites on the surface of the microspheres, which is conducive to the subsequent adsorption of target metal ions; and divinylbenzene, as a cross-linking agent, can form a cross-linked structure between polymer molecules, improving the stability and chemical resistance of the polymer.

[0074] The monomer mixture is added to the magnetic nanoparticle suspension, and the initiator is added after uniform stirring, and the reaction is carried out in an inert atmosphere of 65-75°C (usually nitrogen protection) for 6-8 hours. At this temperature and the action of the initiator, styrene, methacrylic acid and divinylbenzene begin free radical polymerization and gradually polymerize and coat the surface of the magnetic nanoparticles. Due to the presence of the inert atmosphere, the polymerization process can proceed stably, avoiding the interference of oxygen, so that the magnetic nanoparticles can be evenly embedded in the structure of the polymer microspheres, rather than simply attached to the surface of the microspheres. The microspheres embedded with magnetic nanoparticles in this way not only maintain the high specific surface area of ​​the microspheres, but also give them good magnetic responsiveness.

[0075] After the polymerization reaction is completed, the product is centrifuged to remove byproducts such as unreacted monomers and solvents. The microspheres are then washed multiple times with deionized water and ethanol to ensure their purity, and dried under vacuum conditions to obtain the final magnetic polymer microspheres. The microspheres have an embedded magnetic structure, and the magnetic nanoparticles inside them give the microspheres the ability to quickly respond to an external magnetic field, making it easy to use the magnetic field to achieve rapid separation after the metal adsorption process is completed. The magnetic nanoparticles embedded in the magnetic polymer microspheres provide magnetic responsiveness while the magnetic nanoparticles will not be dissolved or agglomerated due to direct contact with the outside world, ensuring the stability of the adsorbent.

[0076] Phosphate groups can be introduced on the surface of magnetic adsorbents by reacting with phosphoric acid or phosphate esters. Specifically, 3-phosphopropyltrimethoxysilane (PPTS) can be used as a modification agent to form a stable phosphate-based layer on the surface of nanoparticles to enhance adsorption capacity. Magnetic adsorbents can be sulfonated with concentrated sulfuric acid to introduce sulfonic acid groups.

[0077] S104: applying a magnetic field to the mixed solution to separate the magnetic adsorbent enriched with target metal ions from the mixed solution.

[0078] By applying external magnetic force, the adsorbent with magnetic nanoparticles quickly gathers on one side of the solution, which is convenient for recovery, filtration and washing, thereby effectively separating the target metal ions. This separation method utilizes the magnetic response characteristics of the magnetic adsorbent, making the target metal separation process more efficient and simple, avoiding the cumbersome operations and equipment requirements in traditional centrifugation or filtration processes.

[0079] The basic principle of applying a magnetic field to separate adsorbents is that magnetic adsorbents undergo a magnetic aggregation effect under the action of an external magnetic field. Magnetic adsorbents contain magnetic nanoparticles (such as cobalt, iron or nickel nanoparticles). When an external magnetic field is applied, these particles will quickly aggregate under the action of the magnetic field force, thereby driving the entire adsorbent to move together. Since these magnetic nanoparticles are embedded or coated in the adsorbent structure, the action of the magnetic field can directly affect the entire adsorbent, allowing it to be quickly separated from the solution. Compared with traditional centrifugal separation methods, magnetic field separation methods are simple and rapid to operate, can complete the complete recovery of adsorbents within a few minutes, and are suitable for large-scale continuous separation.

[0080] In an exemplary embodiment, the separated magnetic adsorbent enriched with target metal ions can be washed; the washed magnetic adsorbent is added to an ethylenediaminetetraacetic acid solution to dissociate the target metal ions enriched on the magnetic adsorbent to obtain a dissociation solution; a magnetic field is applied to the dissociation solution to separate the magnetic adsorbent from the dissociation solution.

[0081] The magnetic adsorbent enriched with the target metal ions is washed to remove any residual impurities or solutions that may exist on the surface of the adsorbent, so as to ensure that the dissociation effect is not affected by the interference of impurities during the dissociation process. Usually, deionized water or ethanol solution is used for washing to avoid the influence of ions or solvent residues on the dissociation reaction.

[0082] The washed magnetic adsorbent is added to an ethylenediaminetetraacetic acid (EDTA) solution to dissociate the target metal ions. EDTA is a chelating agent with four carboxyl groups and two amino groups, which can form a highly stable chelate in solution. This molecular structure enables it to form a strong coordination bond with the target metal ions (such as cobalt, nickel, manganese, etc.), and its stability is much higher than the combination of the target metal ions with phosphate or sulfonic acid groups. By introducing the EDTA solution, the target metal ions adsorbed on the surface of the adsorbent can be chelated with EDTA through competitive complexation to form an EDTA-metal complex dissolved in the dissociation solution. At this time, the concentration and pH value of the EDTA solution are controlled at neutral or weak alkaline to ensure that the coordination reaction between EDTA and metal ions proceeds smoothly. The advantage of using EDTA as a dissociating agent is that it can efficiently dissociate the target metal ions and maintain the stable coordination form of the target metal ions, which is convenient for subsequent recovery and treatment.

[0083] After the target metal ions are dissociated, the magnetic adsorbent is separated from the dissociation solution by applying a magnetic field. The purpose of this step is to quickly separate the adsorbent from the dissociated solution by magnetic separation to facilitate the collection of the target metal ions in the solution. The magnetic adsorbent will quickly aggregate when a magnetic field is applied, while the EDTA-metal complex in the dissociation solution will not be affected by the magnetic field and can be separated smoothly. At this point, the EDTA dissociation solution enriched with the target metal can be further processed to recover the metal, while the magnetic adsorbent can be recovered for the next round of adsorption operation.

[0084] The present invention will be further described below in conjunction with specific embodiments. Example 1

[0085] (1) Preprocessing

[0086] The discarded lithium-ion batteries are completely discharged and disassembled to separate the positive electrode materials. The positive electrode material samples are dried and crushed to less than 100μm.

[0087] (2) Leaching

[0088] The positive electrode material particles obtained by pretreatment were added to the composite solvent (the mass ratio of the positive electrode material particles to the composite solvent was 1:15), and the composite solvent was composed of citric acid (concentration of 1 mol / L) and 2,2'-bipyridine ligand (molar ratio with the target metal ion was 1.3:1). The pH of the solution was adjusted to 3.5 to achieve the best leaching conditions for the target metal ions. After stirring and leaching for 3 hours at 60°C, the leachate containing the target metal ions was filtered and the solid residue was removed.

[0089] (3) Enrichment of target metal ions

[0090] Magnetic polymer microspheres modified with phosphate groups on the surface were added to the leachate as magnetic adsorbents, and the pH of the solution was adjusted to 1.5 to promote the dissociation of metal ions complexed with organic ligands and enhance the enrichment effect of metal ions of phosphate and sulfonic acid groups. After stirring for 1 hour, the target metal ions in the solution were enriched on the adsorbent to obtain a mixed solution. Under stirring conditions, the target metal ions dissociated from the complex and were enriched on the phosphate and sulfonic acid groups on the surface of the magnetic adsorbent.

[0091] (4) Magnetic field separation

[0092] Place the mixed solution next to an electromagnet and apply a magnetic field to separate the magnetic adsorbent enriched with the target metal from the solution. The adsorbent quickly aggregates under the action of the magnetic field to form a solid-liquid separation. Pour off the supernatant and retain the magnetic adsorbent for subsequent processing.

[0093] (5) Dissociation and metal recovery

[0094] The separated magnetic adsorbent enriched with target metals is washed with deionized water to remove surface impurities. The washed adsorbent is added to a 0.1M EDTA solution, and the pH is adjusted to 7 to promote the chelation reaction between EDTA and the target metal ions on the adsorbent surface. The multi-dentate structure of EDTA can effectively dissociate the target metal ions on the adsorbent surface to form a stable EDTA-metal complex.

[0095] After stirring for 30 minutes, a magnetic field is applied to separate the magnetic adsorbent from the dissociation solution. At this time, the dissociation solution contains EDTA-metal complexes enriched with target metal ions. The dissociation solution is collected, the pH is adjusted to 1-2, and a sodium carbonate solution with a concentration of 6.5 mol / L is added to precipitate nickel, cobalt and manganese to obtain a nickel, cobalt and manganese coprecipitate. Example 2

[0096] The difference compared with Example 1 is that the pH value of the solution is adjusted to 5 during the leaching process in this embodiment, and the other steps and conditions are consistent with Example 1. Example 3

[0097] The difference compared with Example 1 is that the pH value of the solution is adjusted to 2.7 during the enrichment of the target metal ions in this example, and the other steps and conditions are consistent with those in Example 1. Example 4

[0098] The difference compared with Example 1 is that the organic ligand in the composite solvent of this example is 1,10-phenanthroline, and the other steps and conditions are consistent with those of Example 1. Example 5

[0099] The difference compared with Example 1 is that the magnetic adsorbent in this example is a magnetic carbon nanotube with a surface modified with a phosphate group, and the rest of the preparation method and conditions are the same as those in Example 1. Example 6

[0100] The difference compared with Example 1 is that the magnetic adsorbent in this example is a magnetic polymer microsphere with sulfonic acid groups modified on the surface, and the rest of the preparation method and conditions are the same as those in Example 1.

[0101] Comparative Example 1

[0102] The difference compared with Example 1 is that the pH value of the solution is adjusted to 3 during the leaching process in this comparative example, and the other steps and conditions are consistent with Example 1.

[0103] Comparative Example 2

[0104] The difference compared with Example 1 is that the pH value of the solution is adjusted to 5.5 during the leaching process in this comparative example, and the other steps and conditions are consistent with Example 1.

[0105] Comparative Example 3

[0106] The difference compared with Example 1 is that the pH value of the solution is adjusted to 3 during the enrichment of the target metal ions in this comparative example, and the other steps and conditions are consistent with those in Example 1.

[0107] Comparative Example 4

[0108] The difference compared with Example 1 is that the solvent used for leaching in this comparative example is citric acid without organic ligands, and the other steps and conditions are consistent with Example 1.

[0109] Comparative Example 5

[0110] The difference compared with Example 1 is that the organic ligand in the composite solvent used for leaching in this comparative example is replaced by pyridine, and the other steps and conditions are consistent with Example 1.

[0111] Comparative Example 6

[0112] The difference compared with Example 1 is that in this comparative example, citric acid in the composite solvent used for leaching is replaced by sulfuric acid, and the remaining steps and conditions are consistent with Example 1.

[0113] Comparative Example 7

[0114] The difference compared with Example 1 is that the magnetic adsorbent in this comparative example is unmodified phosphate and sulfonic acid group magnetic polymer microspheres, and the other steps and conditions are consistent with Example 1.

[0115] Recycling effect evaluation

[0116] The nickel-cobalt-manganese coprecipitates were recovered from Examples 1 to 6 and Comparative Examples 1 to 7, and the chemical composition was tested to analyze the recovery effects of each Example and Comparative Example. The results are shown in Table 1:

[0117] Table 1 - Recovery effect test results

[0118]

[0119] In summary, the method for recovering target metals in lithium battery positive electrode materials provided by the present invention uses a composite solvent system consisting of citric acid and an organic ligand containing two nitrogen heterocycles to achieve efficient leaching of target metal ions under appropriate acidic conditions, wherein citric acid provides a stable acidic environment and the dinitrogen heterocycle ligand enhances the selective complexation of cobalt, nickel and manganese; at the same time, a magnetic adsorbent with a surface modified with phosphate and / or sulfonic acid groups is used to achieve efficient enrichment of target metal ions through pH adjustment, and rapid separation is achieved under an external magnetic field; and the recovery rate and recovery purity of this method are both high.

[0120] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0121] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for recovering target metals in lithium battery positive electrode materials, wherein the target metals include cobalt, nickel and manganese, characterized in that: The method comprises: Pre-treating the lithium battery to obtain positive electrode material particles; The positive electrode material particles are added to a composite solvent, the pH is adjusted to 3.3-5, and the target metal ions are leached to obtain a leachate; the composite solvent comprises citric acid and an organic ligand containing two nitrogen heterocycles, and the organic ligand comprises at least one of 2,2'-bipyridine and 1,10-phenanthroline; Adding a magnetic adsorbent to the leaching solution, adjusting the pH to 1-2.7, so that the target metal ions are enriched on the magnetic adsorbent to form a mixed solution; the surface of the magnetic adsorbent is modified with phosphate groups and / or sulfonic acid groups; A magnetic field is applied to the mixed solution to separate the magnetic adsorbent enriched with target metal ions from the mixed solution.

2. The method for recovering target metal in lithium battery positive electrode material according to claim 1, characterized in that: Methods for pre-processing lithium batteries include: After the lithium battery is fully discharged, it is disassembled and the positive electrode material is separated; The positive electrode material is crushed and sieved to obtain positive electrode material particles with a particle size of less than 100 μm.

3. The method for recovering target metal in lithium battery positive electrode material according to claim 1, characterized in that: The mass ratio of the positive electrode material particles to the composite solvent is 1: (10-20); and / or The concentration of citric acid in the composite solvent is 0.5-1.5 mol / L; and / or The molar ratio of the organic ligand to the target metal ion in the composite solvent is (1-2):

1.

4. The method for recovering target metal in lithium battery positive electrode material according to claim 1, characterized in that: The preparation method of the composite solvent includes: dissolving citric acid in deionized water to obtain a citric acid solution; dissolving an organic ligand in ethanol to obtain an organic ligand solution; The citric acid solution and the organic ligand solution are mixed to obtain a composite solvent.

5. The method for recovering target metal in lithium battery positive electrode material according to claim 1, characterized in that: The magnetic adsorbent includes magnetic carbon nanotubes attached with cobalt and / or nickel nanoparticles.

6. The method for recovering target metal in lithium battery positive electrode material according to claim 5, characterized in that: The preparation method of the magnetic carbon nanotubes comprises: The carbon nanotubes are refluxed in a mixed acid of sulfuric acid and nitric acid for 2 to 6 hours for acidification treatment; Dispersing the acidified carbon nanotubes in a cobalt and / or nickel metal salt solution, and ultrasonically treating for 3 to 8 hours to obtain a carbon nanotube suspension; Under ice bath conditions, adding sodium hydride to the carbon nanotube suspension, stirring the reaction, so that the cobalt and / or nickel metal ions are reduced to metal nanoparticles, which are attached to the surface of the carbon nanotubes; The product is collected by centrifugation, washed and dried to obtain magnetic carbon nanotubes.

7. The method for recovering target metal in lithium battery positive electrode material according to claim 1, characterized in that: The magnetic adsorbent comprises magnetic polymer microspheres, wherein magnetic nanoparticles are embedded in the magnetic polymer microspheres.

8. The method for recovering target metal in lithium battery positive electrode material according to claim 7, characterized in that: The preparation method of the magnetic polymer microspheres comprises: The magnetic nanoparticles were dispersed in an ethanol solution, polyvinyl alcohol was added, and ultrasonic dispersion was performed for 30 minutes to obtain a magnetic nanoparticle suspension; Mix styrene, methacrylic acid and divinylbenzene monomers in proportion to obtain a monomer mixture; The monomer mixture is added to the magnetic nanoparticle suspension, stirred evenly, and then the initiator is added; The mixture was stirred at 65-75°C and in an inert protective atmosphere for 6-8 hours to polymerize styrene, methacrylic acid and divinylbenzene monomers on the surface of the magnetic nanoparticles; The product is collected by centrifugation, washed and dried to obtain magnetic polymer microspheres.

9. The method for recovering target metal in lithium battery positive electrode material according to claim 1, characterized in that: The method further comprises: washing the separated magnetic adsorbent enriched with target metal ions; adding the washed magnetic adsorbent into an ethylenediaminetetraacetic acid solution to dissociate the target metal ions enriched on the magnetic adsorbent to obtain a dissociation solution; A magnetic field is applied to the dissociation solution to separate the magnetic adsorbent from the dissociation solution.

Citation Information

Patent Citations

  • Method for recycling high-value-added metals from waste nickel-cobalt-manganese lithium ion batteries

    CN108913873A